Authors speak - Saccidanandan 1946-.; Sahitya Akademi (New Delhi Sahitya Akademi, 2006)
Lectures delivered by 15 eminent Indian authors on their lives, works, and influences at the "Meet the author" programs organized jointly by Sahitya Akademi and India International Centre, New Delhi; includes selections and translations from their works.
Keywords: Authors, Indic -- 20th century -- Biography; Indic literature -- 20th century -- History and criticism